Pengaruh Kompensasi, Komunikasi, dan Pelatihan Terhadap Semangat Kerja Para Dosen Fakultas Ekonomi dan Bisnis Universitas Balikpapan - Rizal, Sarah; Hadiyatno, Didik; Arrywibowo, Imam (MEDIA RISET EKONOMI [MR.EKO], 2024)
The purpose of this study is to determine the influence of compensation, communication, and training on the work spirit of lecturers in the Faculty of Economics and Business at Balikpapan University. The sampling technique used in this research is census with a sample size of 36 lecturers. Data collection was conducted through the distribution of questionnaires. This research utilizes SmartPLS for data processing. The results of this study indicate that the variable of non-financial compensation does not have a positive and significant impact on the work spirit of lecturers in the Faculty of Economics and Business at Balikpapan University. The communication variable has a positive and significant impact on the work spirit of lecturers in the Faculty of Economics and Business at Balikpapan University. Similarly, the training variable has a positive and significant impact on the work spirit of lecturers in the Faculty of Economics and Business at Balikpapan University.